RESPON PERTUMBUHAN DAN HASIL TANAMAN JAGUNG PULUT (Zea mays ceratina Kulesh) PADA BERBAGAI JARAK TANAM DALAM BARIS - Clemens Pati Nai; Kristono Yohanes Fowo (Agriculture Faculty of Flores University, 2019)
Corn is an important commodity after rice. The need for corn continues to increase every year. It is necessary to increase production, one of them through the use of varieties and optimal population regulation (spacing). This study aims to determine the growth and yield of Pulut (Zea Mays Ceratina Kulesh) F1 Kumala varieties a various spacing in rows. This research was arranged in a Randomized Block Design (RCBD) with the treatments used: J1 = 40 cm x 40 cm, J2 = 50 cm x 40 cm, J3 = 60 cm x 40 cm, J4 = 70 cm x 40 cm, and J5 = 80 cm x 40 cm. The variables observed were plant height, number of leaves, leaf area, the weight of cob without kilobit per plant, the weight of cob without kilobit per ha, ear diameter, ear length, ear weight 100 seeds, and weight of seeds of the crop. The results showed that 70 cm x 40 cm spacing gave a very significant effect. On leaf area (21.85%), the weight of cob without cornhusk per plant (16.76%), ear diameter (4.80%), length cob (10.79%), the weight of 100 seeds (9.18%) and weight of crop seeds (14.97%).